Improving Survival among Preterms: Nsambya Hospital Experience 10 Years - Kirabira, Victoria Nakibuuka; Nazziwa, Ritah; Sebunya, Robert; Baigana, Patrick; Nyagabyaki, Catherine; Nalunga, Sanyu; Ninsiima, Ritah; Santos, Nicole (Gates Open Res, 2019)
Surviving prematurity poses a great challenge in neonatal care in Uganda and Africa at Large and yet it remains the major cause of under-five mortality.While many preterm babies survive in high-income countries, in low- and middle-income countries lack of adequate newborn care puts the lives of many preterm babies at risk. Uganda is ranked 13th among the countries with high preterm birth deliveries worldwide.It is estimated that up to 2/3 of these deaths would be saved if secondary level interventions low cost interventions such as Kangaroo mother care (KMC), Use of antenatal steroids and Continuous positive air way Pressure, Early feeding with breast milk, use of Oxygen are scaled up.
Keywords: Survival; Preterms